SMART GARDEN ONLINE AUTOMATIC PLANT WATERING – IOT CONTROL AND MONITORING TRAINER - Basri, Muhammad Hasan; Akbar , Saiful (International Journal of Multidisciplinary Reseach, 2025)
This research discusses the implementation of an ESP32-based Smart Garden system consisting of two main components, namely a sensor module and a controller module. The sensor module uses a DHT11 sensor to record air temperature and humidity data periodically every hour from 7:00 to 19:00 WIB for seven days. The measurement results show a temperature pattern that increases from morning to noon and decreases in the afternoon, while humidity shows an inverse pattern. The average highest temperature recorded was 29.92 °C on Monday and the lowest temperature was 29.01 °C on Wednesday, with daily humidity ranging from 60.31% to 61.15%. Meanwhile, the controller module functions to regulate plant watering in three operating modes: manual, timer, and automatic. Manual mode allows direct control by the user via buttons, timer mode regulates automatic watering based on a schedule stored in the EEPROM and synchronized with the NTP time, while automatic mode uses fuzzy logic to water based on environmental conditions. The system is also equipped with a battery voltage monitoring feature and a status indicator on the LCD. The test results show that all system components work in an integrated, stable manner, and are able to support intelligent plant watering based on real environmental conditions .